What is the social class of the new small producer ? Political implications of its determination - Lopes, Ana Yara Dania Paulino; Sales, Teresa (Universidade Estadual Paulista / UNESP, 2009)
This paper discusses the theoretical and metodological difficulties to analyse the new producer in Brazilian agriculture.